7th International Immunoglobulin Conference: Immunoglobulin in Clinical Practice. (December 2014) - Shapiro, R. S.; Borte, M.
Summary: Immunoglobulin (Ig) replacement therapy has been the mainstay of primary immunodeficiencies (PID) treatment for more than 30 years and has substantially changed the lives of patients. This review focuses on aspects of Ig use in clinical practice in addition to discussing prioritizing future Ig use. Despite Ig therapy, PID patients continue to be predisposed to recurrent, subclinical respiratory tract infections, which may lead to chronic lung disease. Research has shown that one of the underlying reasons for this deterioration in lung function is the differential distribution and concentration of Ig isotypes in the airway lumen. Further to this, the relationship between Ig dose and infection outcome is explored, expanding on end‐of‐cycle loss of efficacy (wear‐off) particularly with intravenous immunoglobulin (IVIg), how this can confound the determination of optimal IgG dose and how our aim of treatment should be to improve clinical outcome. This review goes on to discuss the safety of Ig replacement therapy, which is generally well tolerated by most patients, compares the rates of systemic adverse reactions between IVIg and SCIg and highlights the advantages of SCIg administration in this respect, including the use of pre‐infused subcutaneous recombinant human hyaluronidase to aid subcutaneous infusion volumes. The growing demand for Ig replacement therapy is challenging physicians; here we show the development of prioritization algorithms to assist in identifying those who will benefit most from this clinically valuable therapy.